الدور السياسي والديني للإله آتون خلال عصر الأسرة الثامنة عشرة (1550 – 1295 ق.م) - صقور براءة (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
God Ra one of the ancient Egyptian Gods how was believed to rule all the world light and radiance. In later Egyptian dynastic times and for his historical status, Ra was merged with number of the major Egyptian Gods such as God Amon-Ra. and also during the Eighteenth Dynasty he reappeared in God Aten. What made Akhenaton during the sixth year of his reign to declare Ra as the only God for Egypt and the whole world. All of this coincided with the religious and political internal and external circumstances, an increase of the priests of Amon authorities and the loss of the Egyptian empire in Syria and Nubia. The research will introduce God Aten, his origin and name, religiously and linguistically. His appearance and development and his relationship with the God Ra. Then we move to his Oneness and his political role as well as his religious activity that was distinguished in construction of temples and the high status of his priests during the reign of Akhenaten. ظهر الإله رع كإله رئيسي لمصر يسيطر على العالم كله بضوئه وأشعته منذ فجر التاريخ المصري، وتم إدماجه مع عدد من الآلهة الرئيسية خلال فترات من تاريخ مصر القديم لمكانته التاريخية مثل "آمون- رع", وعاد للظهور بصورة الإله آتون خلال عصر الأسرة الثامنة عشرة ليعلن إخناتون وحدانيته كإله واحد لمصر والعالم خلال العام السادس من حكمه، والذي ترافق مع ظروف دينية وسياسية داخلية وخارجية، وهي زيادة سلطات كهنة آمون وفقدان الإمبراطورية المصرية في سوريا والنوبة. وسيتناول البحث التعريف بالإله آتون، أصله وتسميته، دينيا ولغويا، ظهوره وتطوره وعلاقته بالإله رع. ثم الانتقال إلى وحدانيته ودوره السياسي. وكذلك إلى النشاط الديني الذي تميز ببناء المعابد وارتفاع مكانة كهنته خلال فترة حكم إخناتون.